2021
DOI: 10.1007/s00167-021-06784-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and reoperation rates after tibial tubercle transfer and medial patellofemoral ligament reconstruction: higher revision stabilization in patients with trochlear dysplasia and patella alta

Abstract: PurposeTo determine the reoperation rate, risk factors for reoperation, and patient‐reported outcomes after isolated or combined tibial tubercle transfer and medial patellofemoral ligament reconstruction, for patellofemoral instability surgery. MethodsPatient’s records who underwent medial patellofemoral ligament reconstruction and/or tibial tubercle transfer for patellar instability by 35 surgeons from 2002 to 2018 at a single academic institution were retrospectively reviewed using CPT codes. Four‐hundred‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The novel 3D classification for trochlear dysplasia was developed to determine whether to perform trochleoplasty for each type. We also realize that the treatments for recurrent patellar instability extend beyond treating trochlear dysplasia [39, 40, 48, 49]. A comprehensive treatment algorithm is needed after assessing osseous and soft tissue risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The novel 3D classification for trochlear dysplasia was developed to determine whether to perform trochleoplasty for each type. We also realize that the treatments for recurrent patellar instability extend beyond treating trochlear dysplasia [39, 40, 48, 49]. A comprehensive treatment algorithm is needed after assessing osseous and soft tissue risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The management of patellar instability is a surgical challenge and requires a tailored surgical strategy to achieve good functional results and a better quality of life [2, 20, 22]. Trochleoplasty in severe Dejour B or D trochlear dysplasia is essential even in the first‐line setting to achieve these results [12, 16, 19, 36, 37, 40]. However, the trochleoplasty technique generally depends on school or habit and does not take into consideration the type of trochlear dysplasia nor the degree of patellar dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al reported female gender was the risk factor for the lower scores of the International Knee Documentation Committee (IKDC) and Kujala score following MPFLr + TTT [ 46 ]. Compared with males, the reoperation rate of females was higher following MPFLr + TTT [ 20 ]. However, Watanabe et al studied the efficacy of MPFLr with or without TTT and found no effect of gender on the results [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The iMPFLr could not achieve promising results due to increased graft tension and potential failure caused by the TT lateralization, which produces anisometry in MPFLr [ 19 ]. Therefore, a combination of MPFLr and TT transfer (TTT) for patients with an increased TT–TG distance, especially when TT–TG distance is greater than 20 mm, should be taken into consideration, with the purpose of addressing both patellar dislocation and patellar maltracking at the same time to restore the optimal position of patella relative to the femoral trochlea [ 5 , 18 , 20 ]. A systematic review showed that MPFLr combined with TTT is a safe and effective surgery, with a low to moderate risk of complications and overall good results [ 21 ].…”
Section: Introductionmentioning
confidence: 99%